An Improved TLBO Algorithm to Solve Profit Based Unit Commitment Problem under Deregulated Environment. (2016) - Krishna, P.V. Rama; Sao, Sukhdeo
Abstract: The TLBO (Teaching learning based optimization technique) is one of the recently developed algorithm and In this paper, an improved TLBO algorithm is proposed to address the profit based unit commitment problem under deregulation. The PBUC problem is one of the major tasks for a power producer and is a highly complex, multi constrained non linear optimization problem. The PBUC involves determining the on/off states of the generating units while satisfying demand and generating unit constraints. Some of the recently developed algorithms like GA, PSO, BBO, ACO etc. are available to solve this complex problem, but so far there is no such ideal technique which can completely address this problem. In this scenario an attempt is made to solve this problem using an improved TLBO. The regular TLBO algorithm is improved by considering some of the factors like teaching factor, number of teachers, learning through tutorials, self motivated learning. The step-by-step procedure of how to apply the improved TLBO algorithm for PBUC problem is presented. The proposed algorithm is tested on IEEE 10 unit 10 hours load demand as input data for simulation using MATLAB R2009a version. From the results obtained it is observed that the improved TLBO algorithm is effective compared to traditional TLBO while handling the computation time and the dimension of the problem.